Karakter Pengelola Keuangan Unit di Program Pendidikan Kompetensi Umum Berdasarkan Pumping HR Model Bagi Kinerja Institusi - Taryani, Heni; Ramly, Amir Tengku (Jurnal Manajemen, 2019)
This paper was made with the aim that the results of the HR-Test Pumping Personality Report that has been carried out can be a reference for character development so that the Unit Financial Manager can begin to improve themselves from the negative results found and continue to increase their potential from the positive results. The positive performance improvement is expected to continue to be carried out so that productivity can run well. Pumping Model-based HR training is a training in human capital which is included in the category of intangible assets. This training is based on personal development, competence, and values of human spirituality. Unit Finance Managers who add insight and skills through various types of training, it is almost certain that it will become human capital, which in the end will increase institutional performance because it has a reliable, skilled and trained Unit Financial Manager.